Optimizing Waste Management Through Multilevel Community Participation - Handini, Widya; Alfitri, Alfitri; Waspodo, Waspodo; Putra, Raniasa (Academia Open, 2025)
General Background: Waste management is a growing urban challenge, particularly in areas experiencing continuous population growth. Specific Background: Sungailiat City faces escalating waste-related issues exacerbated by limited community engagement. Knowledge Gap: Although government programs rely heavily on public participation, there is limited understanding of how effectively communities engage across the different stages of waste policy implementation. Aims: This study aims to analyze the current state of waste management in Sungailiat City and assess the level of community participation in implementing relevant policies. Results: Using a qualitative descriptive approach, the research identifies four levels of participation—decision-making, program implementation, utilization of results, and evaluation—occurring inconsistently across Bangka Regency. Novelty: The study reveals the fragmented and unsystematic nature of participation, evaluated using Cohen and Uphoff’s framework, highlighting a lack of integration across stages. Implications: To promote sustainable waste management, it is essential to institutionalize participatory mechanisms throughout policy cycles, enhance public awareness, and provide robust institutional support through improved infrastructure and regulatory frameworks that foster inclusive community involvement. Highlights: Community participation is crucial for effective waste policy execution. Engagement remains fragmented across different policy stages. Strong institutional support enhances sustainable waste solutions. Keywords: Waste Management, Community Participation, Policy Implementation, Sustainable Development, Sungailiat City